Oxygen uptake during the exercise: temporal aspectos and adjustments of curves - Fernando Roberto de Oliveira; Adriano Eduardo Lima Silva (Universidade Federal de Santa Catarina, 2004)
The oxygen uptake has been considered as one of the most important physiological variables for exercise physiology. The first models relating oxygen uptake with performance emerged in the beginning of last century and it has been intensely discussed in the literature until today. This review discussed some topics about oxygen uptake, more specifically on aspects related with the kinetic and influences of the time response of this variable on the adjustment curve during an incremental test. Discussion on the level of aerobic condition and exercise intensity on the kinetics of oxygen uptake are also included in the text. Finally, verification on the slow component and on the physiological control of the oxygen uptake kinetics is also presented. RESUMO O consumo de oxigênio tem sido considerado uma das variáveis fisiológicas mais importantes para a fisiologia do exercício. Os primeiros modelos relacionando o consumo de oxigênio com o desempenho esportivo surgiram no inicio do século passado e continua sendo intensamente discutido na literatura atual. A presenterevisão discutiu alguns tópicos sobre consumo de oxigênio, mais especificamente sobre aspectos relacionados à cinética e a influencia do tempo de resposta dessa variável sobre os ajustes de curva em teste progressivo. Discussões relacionadas a influencia do nível de aptidão aeróbia e a intensidade do exercício sobre a cinética do consumo de oxigênio também estão inseridas no texto. Por fim, algumas constatações sobre componente lento e os controles fisiológicos da cinética do consumo de oxigênio são abordados.